Implementation of Restorative Justice in Discontinuing Prosecution of Assault Criminal Acts (A Case Study at the Public Prosecutor's Office of Garut) - Ramadhan, Noval; Huda, Uu Nurul; Kurniawan, Wawan (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2024)
The resolution of criminal offenses through restorative justice at the Public Prosecutor's Office of Garut is examined to what extent its implementation is carried out at the Public Prosecutor's Office of Garut. Restorative justice is applied outside the court to settle cases of assault while considering fairness to all parties involved. This study aims to explore how restorative justice is implemented in handling cases of assault at the Public Prosecutor's Office of Garut, as well as the factors influencing its implementation and efforts made to overcome them. The research method used is empirical jurisprudence, which analyzes how the law operates in society. The research findings indicate that the Public Prosecutor's Office of Garut has made efforts to settle cases of assault through restorative justice in accordance with applicable provisions. Supporting factors include the willingness of perpetrators and victims to reconcile, while inhibiting factors include societal views that criminal cases should result in imprisonment. To overcome these obstacles, socialization about restorative justice is conducted to help the community better understand its concepts.